Impact of anti-inflammatory corticosteroids on changes in selected cytoimmunological parameters in selected interstitial lung diseases - Ewelina Wędrowska; Mikołaj Pernak; Mateusz Wędrowski; Violetta Pankowska; Paweł Waśniowski; Elżbieta Piskorska; Walery Zukow (Kazimierz Wielki University, 2019)
Introduction. Glucocorticoids (GKS) hormones with strong immunosuppressive and anti-inflammatory activity are used, inter alia, in interstitial lung diseases (ILD). GKS inhibit excessive activity of inflammatory genes in the airways to induce apoptosis of immune cells, such as alveolar lymphocytes (AL). Objective. Assessment of cytoimmunological changes including apoptosis occurring in alveolar lymphocytes in patients with selected ILD after treatment with systemic corticosteroids. Methods. The material of the bronchoalveolar lavage (BAL) derived from patients with sarcoidosis (PS, n=66), idiopathic pulmonary fibrosis (IPF, n=27) and non-specific interstitial pneumonia (NSIP, n = 25; adequate number of patients treated with systemic GKS were 23, 8 and 6) were analyzed in cytoimmunological tests: a) percentage and the total values of BAL inflammatory cell populations; b) AL subset typing; c) CD4/CD8 index calculation; d) AL cell cycle analysis (DNA staining with propidium iodide, PI); in techniques mentioned in b) to d) items flow cytometry was used. Results. In all patient groups, treatment with GKS resulted in a decrease in the total cell number, e.g. for PS (untreated: 310 ± 80x103/ml; treated: 188 ± 43x103/ml, median ± SEM, p